Estratégias de geoconservação para a proposta geoparque Quarta Colônia - RS - Ziemann, Djulia Regina (2016)
The geoconservation is presented as a important concept because it allows the recognition of the intrinsic value of the geologic and geomorphic, also allows the contemplation of exceptional esthetic value landscapes, that can serve as a tourist attractions, appearing as a positive point the possibility of integration of the local community to be able to initiate the actions of geotourism. This action provides an increase in the local and regional economy. The working capital of the area, based on the concept of sustainability, so that the activity can and will generate economic benefits, conserve the nature and act to improve the life quality of individuals. Therefore, this dissertation looked for contribute and promote local development due to the geoheritage present in the area. Accordingly, we looked for identify, select and characterize the geoheritage present at the Quarta Colonia, we proceeded to realize the identification of: new local tourism, scientific and educational interest. After was created a qualitative assessment and the a pre-selection was made and, concomitantly, there was a characterization and we proceeded to review the geosites present in the inventory previously elaborated by the CPRM. Thus we underwent 43 geosites for the Quarta Colônia, divided by categories, criteria and weights. This procedure allowed we had had knowledge of the degree of representativeness of each geosite, of these 24 sites were identified as suitable to the realization of geotourism and were 19 places that require bigger investments for their future use. We developed also, a geotouristic map to locate the 24 sites most suitable (use according to quantification) for geotouristic. This map was intent for dissemination and exploitation of region's geoheritage. The results of our measurement also showed the great potential of the Quarta Colonia region, mixed with the cultural wealth of colonization provides a clear picture of this territory in the concept of geoparks. Because we have the Quarta Colônia characteristics linked between each other, thank to the identity of the local population to the countryside and its traditional activities; Such as agriculture and livestock, which are adapted according to the geomorphology of that place. Curiously some geomorphological features are used to appoint some cities and used for name of religious events. The tourism nearly not explored of that territory is due to lack of policies that can assist their development and the lack of information of the general public about the benefits that can be generated. Thus, it appears necessary to bring to the local people the importance of their heritage and the possibility of this being used as a basis for sustainable local development, valuing the local culture and the wonderful existing landscapes. A geopark, if implemented within the Quarta Colônia, represents a major promotion strategy for the area, as the geopark is part of a holistic concept of protection, education and sustainable development.